2011
DOI: 10.1002/dc.21426
|View full text |Cite
|
Sign up to set email alerts
|

Pax8: A marker for carcinoma of Müllerian origin in serous effusions

Abstract: PAX8 is a nuclear transcription factor with limited expression in normal and neoplastic tissues in a cell lineage-dependent manner. PAX8 has been detected in embryonic Müllerian ducts, human fallopian tubes, and ovarian carcinomas. However, little is known about its expression in other areas of the female genital tract. In this study, we used immunohistochemistry (IHC) to examine PAX8 expression in the normal uterine corpus and cervix, malignant tumors arising from these sites, and malignant effusions. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 38 publications
3
72
0
Order By: Relevance
“…13,27 In a combined review of 713 primary and 118 metastatic ovarian serous carcinomas from 10 published studies, 650 (91%) and 107 (91%), respectively, were reported to be PAX8 positive. 13,[23][24][25][26][28][29][30][31][32] These results are comparable to those in the present investigation in which 14 (93%) of the 15 primary and 28 (93%) of the 30 metastatic ovarian serous carcinomas were found to express PAX8. To my knowledge, only one study on the expression of PAX8 in peritoneal epithelioid mesotheliomas has been published.…”
Section: Discussionsupporting
confidence: 89%
“…13,27 In a combined review of 713 primary and 118 metastatic ovarian serous carcinomas from 10 published studies, 650 (91%) and 107 (91%), respectively, were reported to be PAX8 positive. 13,[23][24][25][26][28][29][30][31][32] These results are comparable to those in the present investigation in which 14 (93%) of the 15 primary and 28 (93%) of the 30 metastatic ovarian serous carcinomas were found to express PAX8. To my knowledge, only one study on the expression of PAX8 in peritoneal epithelioid mesotheliomas has been published.…”
Section: Discussionsupporting
confidence: 89%
“…Earlier studies showed that PAX8 positivity ranges from 97% to 100% in AIS and 0% to 87% in ECA. [1][2][3][4][5][6][7][8][9] The discrepancies among various studies may be attributable to several factors; the first is small sample size. Our study included 43 ECA (combined 2 cohorts) and 16 AIS, and is one of the largest studies.…”
Section: Comparison Of Pax8 Expression In Eca Versus Uterine Endometrmentioning
confidence: 99%
“…PAX8 is usually expressed in Müllerian tumors and not expressed in many non-Müllerian tumors, including breast, colon, and gastroesophageal cancers. 1,3 Even though PAX8 can also be expressed in kidney, thyroid, and thymus neoplasms, usually these tumors can be differentiated from Müllerian tumors based on morphologic features. 1 During the formation of the reproductive system, paramesonephric ducts (also called Müllerian ducts) differentiate into the oviduct, uterus, cervix, and upper one-third of the vagina.…”
Section: Comparison Of Pax8 Expression In Eca Versus Uterine Endometrmentioning
confidence: 99%
See 1 more Smart Citation
“…18 PAX8 expression is present in the secretory, but not ciliated epithelial cell population of the normal human fallopian tube, 19 and may play a role in differential diagnosis of ovarian epithelial cancers from histologic mimics. [19][20][21][22][23] Calretinin is a recognized mesothelial cell marker, which has been successfully applied to differentiate ovarian serous carcinomas from mesotheliomas, although a few ovarian high-grade serous carcinomas can have weak and focal positivity. [24][25][26] Tubulin identifies cellular surface cilia, and is therefore an appropriate marker to identify ciliated cells.…”
Section: Regular Immunohistochemical Methodsmentioning
confidence: 99%